The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijms23169038
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Internalization Mechanisms and Design Strategies of Arginine-Rich Cell-Penetrating Peptides

Abstract: Cell-penetrating peptides (CPPs) have been discovered to deliver chemical drugs, nucleic acids, and macromolecules to permeate cell membranes, creating a novel route for exogenous substances to enter cells. Up until now, various sequence structures and fundamental action mechanisms of CPPs have been established. Among them, arginine-rich peptides with unique cell penetration properties have attracted substantial scientific attention. Due to the positively charged essential amino acids of the arginine-rich pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 164 publications
(189 reference statements)
1
31
0
Order By: Relevance
“…Arg-rich peptides have been studied as cell-penetrating peptides and used as vehicles to internalize other molecules in eukaryotic cells and as antibacterial peptides with targets within the cell [27,28]. In this context, the interaction with the membrane has been the subject of various studies, due to its internalization capacity without causing membrane disruption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arg-rich peptides have been studied as cell-penetrating peptides and used as vehicles to internalize other molecules in eukaryotic cells and as antibacterial peptides with targets within the cell [27,28]. In this context, the interaction with the membrane has been the subject of various studies, due to its internalization capacity without causing membrane disruption.…”
Section: Discussionmentioning
confidence: 99%
“…It is well demonstrated that Arg-rich membrane-penetrating peptides enter the cell through a mechanism mediated by interaction with the negative groups of membrane lipids. In this mechanism, the exchange of counterions promotes the formation of amphiphilic lipid-amino acid complexes, helping the cell internalization process [27][28][29][30]. In this context, some amino acids seem to favor interaction with the membrane, as is the case of Trp, which has been reported to enhance the interaction of Arg-rich CPPs with membranes due to π-ion pair interactions, also depending on the number of Trp residues present in the sequence, and has been used as a modifier in Arg-rich peptides to increase their internalization capacity [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Cell-penetrating peptides are arginine-rich peptides, and due to their positive charge, they interact with negatively charged drug molecules and cell membranes through non-covalent interaction, including electrostatic interactions. As such, the application of these arginine-rich peptides has been used to deliver biosensors, drugs, and vaccines and allows entry through the blood-brain barrier [ 219 ]. An example is the use of these peptides linked to chemotherapeutic drugs, such as doxorubicin, for its specific delivery to triple-negative breast cancers [ 220 ].…”
Section: Applicationsmentioning
confidence: 99%
“…The guanidine of arginine could form bidentate hydrogen bonds with the negative phosphates, sulfates, and carboxylates on the cell surface and be driven into cells. 11 Our groups also did some explorations in screening the types and structures of amino acids and found that the structure, stability, size, and construction of assemblies also significantly affected the transfection efficiency of lipoplexes, especially in the presence of serum. As well, the hydrophobic tail of lipids mainly affects the assembly, which has been widely studied with a focus on the length ( C ), unsaturation ( Ω ), and the number of alkyl chains ( N ).…”
Section: Introductionmentioning
confidence: 99%